PENYELESAIAN TINDAK PIDANA PENGANIAYAAN MELALUI MEDIASI PENAL BERDASARKAN HUKUM ADAT MELAYU DI DESA KUNTU KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - RINANDA, RIFAN; Artina, Dessy; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Penal mediation is known in the criminal justice system in Indonesia due to the thought associated with the ideas of reforming criminal law (penal reform), and is associated with the problem of pragmatism or legal rigidity in answering the problems that exist in society. The background of pragmatism is to reduce the stagnation or accumulation of cases. The reasoning mediation is the restorative justice process in criminal law which is carried out by mediating between the perpetrator and the victim with a purpose. In the perspective of legal sociology and culture-oriented, people in Indonesia in general, especially in Gorontalo District have a conflict resolution mechanism based on customs which always puts forward problem solving together with the aim to improve or harmonize with the way of the conference that is to bring the perpetrators and victims together. family of both parties and community leaders.This type of research can be classified in the type of sociological legal research (empirical), because in this study the author immediately conducts research on the location or place under study in order to provide a complete and clear picture of the problem under study. This research was carried out in the Riau Regional Police jurisdiction, while the population and samples were the Riau Regional Police, Investigators of the Riau Regional Police and Actors of Narcotics. The data sources used are primary data, and secondary data. Data collection techniques in this study were interviews, questionnaires, and literature review.The conclusions that can be obtained from the results of the study are: First, an active representative from Babinkamtibmas is needed to create safe conditions and provide understanding to the public about the needs of safe conditions. Secondly, in order that legislators must also look at the laws that live within the community so that they do not overlap at the level of implementation Third, important factors and constraints namely that legislators must also socialize programs and laws for the community.Keywords: Penal Mediation, Melayu Customary Law, Criminal Acts of Abuse.